2022
DOI: 10.3390/molecules27051481
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product-Based Potential Therapeutic Interventions of Pulmonary Fibrosis

Abstract: Pulmonary fibrosis (PF) is a disease-refractive lung condition with an increased rate of mortality. The potential factors causing PF include viral infections, radiation exposure, and toxic airborne chemicals. Idiopathic PF (IPF) is related to pneumonia affecting the elderly and is characterized by recurring scar formation in the lungs. An impaired wound healing process, defined by the dysregulated aggregation of extracellular matrix components, triggers fibrotic scar formation in the lungs. The potential patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 241 publications
(259 reference statements)
0
15
0
Order By: Relevance
“…The potential benefits of natural products include their robust safety standards and numerous biological properties, which are vital elements in the prevention and treatment of pulmonary fibrosis. 27 Accordingly, natural products with potent anti-inflammatory effects were considered for preventing pulmonary fibrosis in COVID-19 patients. 26 Thus, we investigated the protective impact of BET, the most abundant compound in beetroot, against the NLRP3-mediated EMT in BLM-induced pulmonary fibrosis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of natural products include their robust safety standards and numerous biological properties, which are vital elements in the prevention and treatment of pulmonary fibrosis. 27 Accordingly, natural products with potent anti-inflammatory effects were considered for preventing pulmonary fibrosis in COVID-19 patients. 26 Thus, we investigated the protective impact of BET, the most abundant compound in beetroot, against the NLRP3-mediated EMT in BLM-induced pulmonary fibrosis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…An excessive release of these pro-inflammatory cytokines may activate another important signaling pathway that is involved in inflammation and tissue repair and also in fibrosis in the case of excessive activation, which is modulated by the growth factors TGF-β [ 20 ] and VEGF [ 21 ]. TGF-β is a classical pro-fibrotic factor that provides a key role in wound healing when present at physiological levels [ 22 ]. On the other hand, excessive levels of TGF-β result in an impaired wound-healing process characterized by the dysregulated aggregation of extracellular matrix components, triggering fibrotic scar formation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is a classical pro-fibrotic factor that provides a key role in wound healing when present at physiological levels [ 22 ]. On the other hand, excessive levels of TGF-β result in an impaired wound-healing process characterized by the dysregulated aggregation of extracellular matrix components, triggering fibrotic scar formation [ 22 ]. In the present study, it was found that LPS stimulation plus hydrolyzed collagen in fibroblasts and keratinocytes induced an increase in the expression of TGF-β, demonstrating for the first time that hydrolyzed collagen-induced TGF-β expression.…”
Section: Discussionmentioning
confidence: 99%
“…This mediator is most commonly involved in the mechanism of lung fibrosis. 52 There has been previous research on this using HYSA for treating lung fibrosis. Previous research with mice reported that HYSA reduces expression of TGF-β, α-smooth muscle actin, and collagen I mRNA levels.…”
Section: Lung Fibrosismentioning
confidence: 99%